Microcephaly, an etiopathogenic vision - Luis Eduardo Becerra-Solano; Leovigildo Mateos-Sánchez; Eunice López-Muñoz (Elsevier, 2021)
Microcephaly is defined by an occipital-frontal head circumference (OFD) 2 standard deviations (SD) smaller than the average expected for age, gender and population. Its incidence has been reported between 1.3 and 150 cases per 100,000 births. Currently, new clinical characteristics, causes and pathophysiological mechanisms related to microcephaly continue to be identified. Its etiology is varied and heterogeneous, with genetic and non-genetic factors that produce alterations in differentiation, proliferation, migration, repair of damage to deoxyribonucleic acid and neuronal apoptosis. It requires a multidisciplinary diagnostic approach that includes a medical history, detailed prenatal and postnatal clinical evaluation, cerebral magnetic resonance imaging, neuropsychological evaluation, and in some cases complementary tests such as metabolic screening, tests to rule out infectious processes and genetic testing. There is no specific treatment or intervention to increase cerebral growth; however, timely intervention strategies and programs can be established to improve motor and neurocognitive development, as well as to provide genetic counseling. The objective of this work is to review the available information and reinforce the proposal to carry out an etiopathogenic approach for microcephaly diagnosis and management.